2021
DOI: 10.1016/j.jcmgh.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

6-Gingerol Ameliorates Hepatic Steatosis via HNF4α/miR-467b-3p/GPAT1 Cascade

Abstract: BACKGROUND & AIMS:The development of nonalcoholic fatty liver disease (NAFLD) can be modulated by microRNAs (miRNA). Dietary polyphenols modulate the expression of miRNA such as miR-467b-3p in the liver. In addition, 6-gingerol (6-G), the functional polyphenol of ginger, has been reported to ameliorate hepatic steatosis; however, the exact mechanism involved and the role of miRNA remain elusive. In this study, we assessed the role of miR-467b-3p in the pathogenesis of hepatic steatosis and the regulation of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Importantly, our investigation showed that gingerol inhibited the increase in miR‐210 expression observed in response to hypoxia/reoxygenation, indicating that miR‐210 might be the mediator of the protective effect of gingerol on hypoxia/reoxygenation‐stimulated neuronal cells. Two reports 35,36 indicate that the potential mechanism by which gingerol alters miR‐210 expression is mediated by upstream factors such as lncRNAs or transcription factors, which should be investigated in future studies. miR‐210 is upregulated in acute cerebral ischemia (ACI), indicating the potential role of this miRNA in ACI diagnosis, according to a previous investigation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our investigation showed that gingerol inhibited the increase in miR‐210 expression observed in response to hypoxia/reoxygenation, indicating that miR‐210 might be the mediator of the protective effect of gingerol on hypoxia/reoxygenation‐stimulated neuronal cells. Two reports 35,36 indicate that the potential mechanism by which gingerol alters miR‐210 expression is mediated by upstream factors such as lncRNAs or transcription factors, which should be investigated in future studies. miR‐210 is upregulated in acute cerebral ischemia (ACI), indicating the potential role of this miRNA in ACI diagnosis, according to a previous investigation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…We selected FFA-induced BRL cells (oleate and palmitate ratio was 2:1) to establish a cellular NAFLD model, which is a widely used method by researchers for studying diseases related to hepatocytes lipid accumulation [ 18 ]. The TG secretion was measured to preliminarily evaluate the inhibitory effect on lipid accumulation of 15 isolated alkaloid compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the docking analysis, we found that the potential binding of 6-gingerol and LKB1 with favorable binding energies might account for the increasing stability of the LKB1/STRAD/MO25 complex, which, however, warrants future validation. What is more, it has been reported that 6-gingerol ameliorates hepatic steatosis via the HNF4α/miR-467b-3p/GPT1 pathway [ 24 ], which provides another research strategy. Moreover, our drug efficacy mainly concentrates in the amelioration of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…6-Gingerol (6-G, PubChem CID: 442793), one of the major pharmacologically active ingredients extracted from ginger, has been found to have pleiotropic pharmacological functions, including anti-oxidative [ 17 ], anti-inflammatory [ 18 ], anti-obesity, anti-cancer [ 19 , 20 ], anti-hyperglycemic and immunomodulatory [ 21 , 22 ] effects. Previously, 6-gingerol was reported experimentally to alleviate hepatic steatosis in HFD-fed mice [ 23 , 24 ], as well as to mitigate intracellular lipid accumulation and to activate AMPK in free fatty acid (FFA)-induced Hepa1–6 cells [ 24 ]. It has been reported that 6-gingerol modulates the inflammatory status and the metabolic disorders in HFD-fed rats, which is associated with a 6-gingerol-induced activating effect on hepatic AMPK [ 25 ].…”
Section: Introductionmentioning
confidence: 99%